ANALISIS PENGARUH BEBAN KERJA PERAWAT TERHADAP KUALITAS PELAYANAN KEPERAWATAN RSUD KOTA PADANGSIDIMPUAN - Suryani, Elvi; Rambe, Normayanti (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The workload given determines a nurse can carry out nursing care well or not. Nurses who have more workload than they should, meaning doing other work outside of nursing that results in the quality of nursing services can not achieve optimal results. Types in quantitative research with cross-sectional approach. The population in this study was all implementing nurses in the inpatient room class I Padangsidimpuan Regional General Hospital as many as 30 people using total sampling techniques. Hypothesis test using Chi-Square test. The result of the study is that the quality of nursing services in the Inpatient Room Class I Padangsidimpuan City General Hospital is sufficient and the workload of nurses average - the average productive nursing conducted has not been effective. The result of the study is that the quality of nursing services in the Inpatient Room Class I Padangsidimpuan City General Hospital is sufficient and the workload of nurses average - the average productive nursing conducted has not been effective. The results of the analysis obtained a value of p = 0.001 shows a relationship between the workload of implementing nurses and the quality of nursing services. In this study, the management of Padangsidimpuan Regional Hospital must equip facilities and infrastructure to support nursing services and be a consideration in the nursing management department to take policy in adding energy gradually in each inpatient room based on wins method.